Pengaruh E-Commerce Dan Penggunaan Sistem Informasi Akuntansi Terhadap Pengambilan Keputusan Berwirausaha - Dwi Erna Yuliani; Risca Azmiana (Economics and Digital Business Review, 2024)
This study aims to obtain evidence regarding the influence of e-commerce on entrepreneurial decision-making, the effect of using accounting information systems on entrepreneurial decision-making. This research was conducted at a university in the city of Batam. The collection of data used in this study is a questionnaire. The population in this study were students majoring in accounting with active student status. The data used in this study is primary data obtained by distributing questionnaires directly to 100 respondents who are determined using the solving formula with purposive sampling method. The results of the analysis show that e- commerce has a positive effect on entrepreneurial decision-making, the use of accounting information systems has a positive effect on entrepreneurial decision-making, and e-commerce and the use of accounting information systems have a positive effect on entrepreneurial decision-making.